Discovery of a novel RSK2 inhibitor for the treatment of metastatic pancreatic cancer - Chi-Hsiu Chung; Kai-Cheng Hsu; Ming-Min Huang; Huang-Ju Tu; Shiow-Lin Pan; Min-Wu Chao (Journal of Enzyme Inhibition and Medicinal Chemistry)
Pancreatic cancer is among the most lethal malignancies, with a five-year survival rate of only 6%. For patients with metastatic disease, current treatments extend median survival by merely four months. This study addresses the urgent need for targeted therapies, as no specific drugs are currently available. Clinical analyses revealed significantly elevated RSK2 expression in pancreatic cancer tissues, associated with shorter survival. We aimed to identify a novel RSK2 inhibitor for metastatic pancreatic cancer. Through structure-based virtual screening, we identified NSYSU-115 as a promising candidate with an IC50 of 45.5 nM. At low concentrations, NSYSU-115 significantly suppressed colony formation, while higher concentrations reduced cell viability and proliferation. It also inhibited phosphorylation of IκBα, a known RSK2 substrate, in a dose- and time-dependent manner. Furthermore, NSYSU-115 impaired cell migration and altered epithelial-mesenchymal transition (EMT) markers. These findings highlight NSYSU-115 as a potent kinase inhibitor with promising therapeutic potential for pancreatic cancer treatment.